Response of three species of Salix to different soil types and water content - Mea, Luiz Gustavo Wiles Della; Rech, Tássio Dresch; Boff, Mari Inês Carissimi; Nunes, Marcelo Zanellato (Revista de Ciências Agroveterinárias, 2014)
This work aimed to study the response of tree willow species to different water soil contents. The experiment was conducted inside a greenhouse using a completely randomized design, in a factorial arrangement of 2 x 3 x 4 with four replicates. Biomass production of Salix x rubens, Salix viminalis and Salix smithiana was higher when the moisture retention capacity of the soil was close to 100%.